Understanding Student’s Learning & e-Learning Style Before University Enrollment: A Case Study in Five High Schools / Sulaimani-KRG - Ghareb, Mazen Ismaeel; Karim, Sazgar Hamameen; Ahmed, Zanyar Ali; Kakbra, Jamal (Kurdistan Journal of Applied Research, 2017)
In spite of the advantages of e-learning which have been talked about in different past researches; it is a basic issue to better understand the reasons why a few numbers of students have been disappointed with the e-learning background. Along these lines, these examinations of the researches among students are fulfillment, behavioral goals, and the adequacy of the conventional learning framework that KRG utilizes with worldwide using of e-learning system. A total of 500 secondary school students of 11 and 12 grades was surveyed using a standard survey of questionnaires. The outcomes demonstrated that apparent self-viability is a basic factor that impacts students’ fulfillment with the e-learning framework and shows how the customary framework has numerous disadvantages. Seen convenience and saw fulfillment both add the student’s behavioral expectation to utilize the e-learning framework. Besides, e-learning viability can be affected by multimedia guideline, intuitive learning exercises, and e-learning framework quality. This examination proposes an applied model for student’s fulfillment, behavioral aim, and viability of utilizing the e-learning framework before enrolling in the university.